Methods of Using Innovative Game Practice in Extracurricular Physical Education of 5th-Graders - С. І. Марченко; С. С. Козарь (OVS LLC, 2015)
The purpose of the research is to ground the organizational and pedagogical conditions of use of innovative game practice in extracurricular physical education of 5th graders (by the example of SNAG). Research methods. Theoretical analysis and collation of literature sources, sociological analysis, pedagogical experiment, methods of mathematical statistics. Research results. The introduction of a minigolf section in the extracurricular work at Kharkiv gymnasium No. 144 brought about the 64% increase in the number of pupils of the experimantal class attending extracurricular forms of physical education, while the pupils of the reference class increased in numbers only by 7%. Some pupils attended with pleasure both the dancing club and the SNAG section. The results reliably showed that, compared to the beginning of the research, the experimental group manifested improvement (almost 2.5 times) of the state of special physical readiness (increased minigolf target hit rate). The indicators of the overall intermuscular coordination improved too, showing better results than in the reference group (by 15.65%) in hitting the target with a small ball (p < 0,05).